Fungsi Tradisi Nyadran di Desa Bumi Arum Majasto: Teori William. R. Bascom - Pitaloka, Diana (STKIP PGRI Ponorogo Press, 2024)
Tradition is an action or deed that is carried out continuously by a person or group that is considered beneficial. Traditions are old and come from ancestors (Simanjuntak, BA: 2016). The tradition of